N'-(3-Bromo-5-chloro-2-hydroxybenzylidine)-2-hydroxybenzohydrazide - Ariffin, Azhar; Ng, S.W.; Yehye, W.A.; Rahman, N.A. (International Union of Crystallography, 2008)
In the approximately planar title molecule, C(14)H(10)BrClN(3)O(2), the dihedral angle between the aromatic ring planes is 5.79 (12)degrees. The conformation is stabilized by intramolecular O-H center dot center dot center dot N and N-H center dot center dot center dot O hydrogen bonds and an intermolecular O-H center dot center dot center dot O link leads to chains in the crystal propagating in [001].